The chosen. Season two [videorecording (DVD)] - Jenkins, Dallas (Vision Video, 2021)
The word is spreading that Jesus is the Messiah. Increased fame brings growing crowds, new disciples, and more miracles. It also brings trouble. Mary is confronted with old demons. The tension between Simon and Matthew explodes. James and John battle their prejudices and fiery tempers. But they all continue to passionately pursue the man they don₂t always understand but will always follow.